Confronting Drought in Africa’s Drylands : Opportunities for Enhancing Resilience - Cervigni, Raffaello; Morris, Michael (Washington, DC: World Bank; and Agence Française de Développement, 2016)
Drylands make up about 43 percent of the region’s land surface, account for about 75 percent of the area used for agriculture, and are home to about 50 percent of the population, including many poor. Involving complex interactions among many factors, vulnerability in drylands is rising, jeopardizing the livelihood for of millions.